Evaluation of the Naturally Acquired Antibody Immune Response to the Pv200L N-terminal Fragment of Plasmodium vivax Merozoite Surface Protein-1 in Four Areas of the Amazon Region of Brazil - Storti-Melo, Luciane M.; Souza-Neiras, Wanessa C.; Cassiano, Gustavo C.; Taveira, Leonardo C.; Cordeiro, Antonio J.; Couto, Vanja S. C. A.; Povoa, Marinete M.; Cunha, Maristela G.; Echeverry, Diana M.; Rossit, Andrea R. B.; Arevalo-Herrera, Myriam; Herrera, Socrates; et al. (Amer Soc Trop Med & Hygiene, 2011)
Frequency and levels of IgG antibodies to an N-terminal fragment of the Plasmodium vivax MSP-1 (Pv200L) protein, in individuals naturally exposed to malaria in four endemic areas of Brazil, were evaluated by enzyme-linked immunosorbent assay. Plasma samples of 261 P vivax-infected individuals from communities of Macapa, Novo Repartimento, Porto Velho, and Placido de Castro in the Amazonian region with different malaria transmission intensities. A high mean number of studied individuals (89.3%) presented with antibodies to the Pv200L that correlated with the number of previous malaria infections; there were significant differences in the frequency of the responders (71.9-98.7) and in the antibody levels (1:200-1:51,200) among the four study areas. Results of this study provide evidence that Pv200L is a naturally immunogenic fragment of the PvMSP-1 and is associated with the degree of exposure to parasites. The fine specificity of antibodies to Pv200L is currently being assessed.